Acrylated Epoxidized Soybean Oil as a Green Alternative Healant in Development of Autonomous Self-Healing Materials - Saman, Nornadila Mohd; Ang, Desmond Teck Chye; Gan, Seng Neon (Springer, 2019)
Progresses in the development of self-healing materials have resulted in transition from repairing damaged materials via external interference to autonomous internal healing process. This paper explores reaction between acrylated expoxidized soybean oil (AESO) with pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) hardener, followed by microencapsulation of AESO for its potential use in a novel self-healing system. Self-healing reaction involving AESO and PETMP is considered more environmentally friendly than most of the reported self-healing reactions not only because AESO is derived from renewable resources, but also due to the fact that the reaction does not rely on any heavy metal catalyst. Such catalysts are usually introduced in a self-healing system to speed up the intended healing process and it could be very harmful to the environment and also to the end users. It was found that AESO and PETMP are able to crosslink with each other and solidify at room temperature within 15 min of mixing. The reaction occurs readily at room temperature without any external interference, suggesting the viability of the reaction to be utilized in an autonomous self-healing system. This paper follows through with microencapsulation of AESO in melamine-urea-formaldehyde, and result of the characterizations reveal that the microcapsules obtained are spherical with average diameter of around 150 µm, free-flowing, thermally stable at temperature up to 200 °C, and the calculated % of microencapsulation reached as high as 86.4%. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.